PCSK9 Functions in Atherosclerosis Are Not Limited to Plasmatic LDL-Cholesterol Regulation - Luquero, Aureli; Badimon, Lina; Borrell-Pages, Maria (Frontiers in Cardiovascular Medicine, 2021)
The relevance of PCSK9 in atherosclerosis progression is demonstrated by the benefits observed in patients that have followed PCSK9-targeted therapies. The impact of these therapies is attributed to the plasma lipid-lowering effect induced when LDLR hepatic expression levels are recovered after the suppression of soluble PCSK9. Different studies show that PCSK9 is involved in other mechanisms that take place at different stages during atherosclerosis development. Indeed, PCSK9 regulates the expression of key receptors expressed in macrophages that contribute to lipid-loading, foam cell formation and atherosclerotic plaque formation. PCSK9 is also a regulator of vascular inflammation and its expression correlates with pro-inflammatory cytokines release, inflammatory cell recruitment and plaque destabilization. Furthermore, anti-PCSK9 approaches have demonstrated that by inhibiting PCSK9 activity, the progression of atherosclerotic disease is diminished. PCSK9 also modulates thrombosis by modifying platelets steady-state, leukocyte recruitment and clot formation. In this review we evaluate recent findings on PCSK9 functions in cardiovascular diseases beyond LDL-cholesterol plasma levels regulation.